Analisis Materi Ajar Kimia SMA/MA Kelas XI Pada Konsep Termokimia - Gusmilasari Gusmilasari; Abdul Hadjranul Fatah; Maya Erliza Anggraeni (Jurnal Ilmiah Kanderang Tingang, 2020)
This study aims to describe the suitability of the thermochemical concept in the teaching material of SMA / MA Class XI chemistry with the 2013 curriculum and describe the macro structure of discourse and propositions that have the potential for concept errors. The instruments used are concept label identification tables and micro-macro propositions, discourse macro structure models, and identification table propositions that have the potential for concept errors. Data were analyzed descriptively. The results showed that the same concept labels found in textbook A and text book B totaled 22 that were in accordance with the 2013 curriculum. The concept labels that corresponded with the 2013 curriculum in textbook A and text book B each amounted to 15 concept labels and 13 labels concept. Macro structure of discourse in text book A, the discussion of concepts in the elaboration dimension reaches level 5 and the dimensions of progression at level 2, there are 6 concepts, while in text book B the discussion of concepts at the elaboration dimension reaches level 6 and the dimensions of progression at level 2 there are 4 concepts.